1996
DOI: 10.1111/j.1748-5827.1996.tb01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Maxillectomy and targeted radionuclide therapy with 153Sm‐EDTMP in a recurrent canine osteosarcoma

Abstract: An eight-year-old dog with a local relapse of an osteosarcoma was treated with partial maxillectomy and systemic radionuclide therapy that involved two injections, 43 and 45 megabecquerels per kg bodyweight of the bone-seeking agent samarium-153-ethylenediaminetetramethylene phosphonic acid (153Sm-EDTMP), 15 weeks apart. A transient drop in white blood cell count and platelet count was observed following each 153Sm-EDTMP treatment. Follow-up 21 months after surgery revealed no evidence of local recurrence or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…These findings are in agreement with reports in the literature on the effects of Sm-153-EDTMP on blood parameters 12,13,19 .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are in agreement with reports in the literature on the effects of Sm-153-EDTMP on blood parameters 12,13,19 .…”
Section: Resultssupporting
confidence: 83%
“…Evaluation of Sm-153-EDTMP combined with other treatment modalities, as reported by Moe et al 19 , may hold more promise, as well as investigation into other beta-emitting radio-pharmaceuticals 14,16 . The right scapula nevertheless showed more up-take than the opposite scapula.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This agent was initially developed to treat painful bone metastasis, usually in the setting of palliation for diseases like prostate and breast cancer 63 . Brulan and colleagues proved the principal that this agent could be used for osteosarcoma using the companion canine model, an observation confirmed by other studies 64-66 . Subsequently, Pete Anderson and others have shown the utility of this agent in treating human osteosarcoma 67-69 .…”
Section: Samarium and Bisphosphonatesmentioning
confidence: 65%
“…In addition, 153 Sm-EDTMP has also been shown to slow the progression of metastatic disease, due to eradication of smaller lesions [10,11]. Canine studies and limited studies in people have suggested that 153 Sm-EDTMP may also be an effective component of a multi-modality treatment regimen for primary bone tumors [2,[12][13][14][15][16][17]. A clinical trial by Lattimer et al was the first published study that evaluated the therapeutic efficacy that a single or double injection of 153 Sm-EDTMP had on the regression of primary bone tumors [2].…”
mentioning
confidence: 99%